ANALYZING THE BLT POLICY’S EFFECTS DURING THE PANDEMIC ERA: AN ISLAMIC ECONOMIC PERSPECTIVE STUDY - Amin, Khairil; Tarigan, Azhari Akmal; Nurbaiti, Nurbaiti (International Journal Labs, 2022)
Background: Direct cash assistance in Indonesia is organized by a mechanism in the form of compensation for cash, food, health insurance, and education with a target of three levels. Almost poor, poor, very poor. BLT was first held in Indonesia in 2005. Aims: This study aims to analyze the impact of the direct cash assistance program policy in the era of the COVID-19 pandemic with a review of the Islamic economic perspective. Method: This type of research uses a qualitative approach that produces descriptive data in the form of words from interviews conducted by the author to village officials and recipients of direct cash assistance. Findings: The results of this study indicate that, during the covid-19 pandemic, the government provided assistance in cash which was shown to the groups most affected by COVID-19, including the poor, formal workers, and online transportation business actors. And economically, the provision of BLT can only meet the needs of the community within a period of 2 weeks and cannot help the community to meet the needs within a period of 1 month as determined, and after that BLT cannot increase people's income, and this assistance also cannot be used for working capital.